If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z + -5 = 7z + -9 + -1z Reorder the terms: -5 + z = 7z + -9 + -1z Reorder the terms: -5 + z = -9 + 7z + -1z Combine like terms: 7z + -1z = 6z -5 + z = -9 + 6z Solving -5 + z = -9 + 6z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-6z' to each side of the equation. -5 + z + -6z = -9 + 6z + -6z Combine like terms: z + -6z = -5z -5 + -5z = -9 + 6z + -6z Combine like terms: 6z + -6z = 0 -5 + -5z = -9 + 0 -5 + -5z = -9 Add '5' to each side of the equation. -5 + 5 + -5z = -9 + 5 Combine like terms: -5 + 5 = 0 0 + -5z = -9 + 5 -5z = -9 + 5 Combine like terms: -9 + 5 = -4 -5z = -4 Divide each side by '-5'. z = 0.8 Simplifying z = 0.8
| x-6=7x | | x=5my-7b | | 8x+3-7x=11 | | 16w^2+27=0 | | 36x^2+12x+64=0 | | 12=8n-1 | | 3w-11w=48 | | 6=4x-9y | | 5(1.2k+6)=7.1+34.4 | | -7(6x+1)=-133 | | (9x^2)-252x+330=0 | | x-4x+3=-30 | | -3(3n-8)=30 | | p=-3*4+1 | | 3.2/16= | | (3x-4w)(5x-8w)= | | 8-4x=9-5x | | p=-3q+1 | | -3(4-3y)=3y+6 | | 2(6x+8)-5=12x+11 | | (2+3)x(3+3)=x | | 0.51m+0.03=0.4m-0.74 | | -7(k-1)-5=-2(k-6) | | 26=6(5+-1a) | | 7x+15=3(2-y) | | 5z+15=4z+5 | | y^2+4=400 | | [x/3-6]=(2x+4)(-1/2) | | 8y-3=-3 | | 20=3-(z+10) | | 3x+30=x | | -3(t-2)+9t=8t-6 |